Calidad de mercado y reformas al sistema transaccional. El Caso de X-Stream en el Mercado accionario colombiano (2013)
We estimate the effect of the new trading system, X-Stream, on the market quality of the Colombian Stock Exchange on February 2009. We test the effect on liquidity measures (bid-ask margin and price impact), daily and intraday volatility and trading activity, using mean tests, panel data and conditional variance models. We use a proprietary database of transactional and order data from the exchange. The evidence is consistent with X-Stream improving liquidity and reducing volatility in the overall market and on most of the most liquid stocks. These results support the investment on more sophisticated trading systems in Emerging Markets.